Low-voltage electrical installations :
The requirements of this part of IEC 60364 apply to fixed electrical installations inside and outdoors of agricultural and horticultural premises. Some of the requirements are also applicable to other locations that are in common buildings belonging to the agricultural and horticultural premises. Rooms, locations and areas for household applications and similar are not covered by this standard. If some of the special requirements of Part 705 are also applicable for residences and other locations in such common buildings this is stated in the normative text